Ahab, Ulysses, and the white whale: Vittorio Gassman’s adaptation of Moby-Dick - MARIANI, Giorgio (Università di Verona, 2015)
Il saggio analizza alcuni aspetti e problemi sollevati dall'adattamento teatrale del capolavoro di Melville da parte di Vittorio Gassman, con particolare attenzione all'accostamento proposto tra la figura di Ulisse e quella del capitano Ahab. The essay investigates some features and issues raised by Vittorio Gassman's adaptation for the stage of Melville's masterpiece. Specific attention is paid to the conjunction of the figures of Ulysses, on the one hand, and of Captain Ahab, on the other.